Color Pupillography in Dorsal Midbrain Syndrome. Issue 3 (September 2017) - Kelbsch, Carina B.; Maeda, Fumiatsu; Strasser, Torsten; Peters, Tobias M.; Wilhelm, Barbara J. C.; Wilhelm, Helmut M.
Abstract : Objective: The purpose of this study was to evaluate the pupil response to chromatic stimuli in patients with lesions in the dorsal midbrain and possibly gain new insights into the afferent pupillary pathways. Methods: Color pupillography was performed in 5 patients with dorsal midbrain syndrome (DMS), and their results were compared with those of 20 healthy control subjects. We used full-field red stimuli (605 nm) that primarily address the rod/cone system and blue stimuli (420 nm) that preferentially activate intrinsically photosensitive retinal ganglion cells (ipRGCs) directly, with a duration of 4 seconds and a stimulus intensity of 28 lx corneal illumination under mesopic conditions. One eye was stimulated, and the consensual pupil response was recorded and analyzed. Results: The pupillary light reflex in patients with DMS was reduced, differed in shape, and showed a prolonged latency time compared to normal subjects. The blue response was less affected than the red response: the mean maximal relative amplitude (M) was 15.8% (SD = 7.8) in patients with DMS compared with 43.0% (SD = 5.5) in normal subjects for red stimulation, and M = 40.8%, SD = 8.4 (DMS) with M = 58.3%, SD = 4.8 (normals) for blue stimulation. The reduction was 63% for red stimulation but only 30% for blue stimulation in patients with DMS. Moreover, there was a preserved postillumination pupil response to blue stimulation in DMS patients. Conclusions: In DMS, the melanopsin-mediated ipRGC pathway appeared relatively preserved.